Raising Literacy from 20 Percent to 80 Percent? A Science-Based Strategy for GPE Partner Countries - Abadzi, Helen (World Bank, Washington, DC, 2013)
Governments and donors have been working hard to develop efficient learning programs and resolve the learning crisis. Scientific lessons have already been implemented in a few countries. Global Partnership for Education (GPE) gave technical advice to Cambodia and the Gambia on reading (also on math); the reading pilots resulted in very satisfactory outcomes and expressions of appreciation by governments. Not surprisingly, other GPE partner countries have directly requested technical advice. With sharp messages and close coordination, the current mountain of problems can be reduced to a molehill in five years. Basic reading can be taught efficiently and quickly, by the middle of grade one. If such an outcome seems unbelievable, it is only because reading is taught through models tailor-made for certain western European languages. Students are to learn basic reading in local languages within the first 100 days of grade one. At the same time, they will learn the official language orally. In grade two they will receive a bridging course to transition eventually to the formal language. The many older illiterate students are to be remediated through the same 100-day program ('literate school in 100 days') and similarly receive a bridging course to the official language. One issue that is often voiced by government officials is that language of instruction for early grade reading is desirable, but students should exit early and not spend years studying in a local language. Given the need for basic literacy, it is certainly possible to follow the policy option that government's desire. In higher-income countries, students get exposed to print before school, so they progress fast in automaticity and text interpretation. Commensurately, the poor are expected to progress quickly into meaning and content. The early learning failure in low income countries is due to missing 'low level' building-block skills.